A jackass and a fish: A case of life-threatening intentional ingestion of a live pet catfish (Corydoras aeneus). Issue 1 (1st January 2019) - Benoist, Linda B. L.; van der Hoven, Ben; de Vries, Annemarie C.; Pullens, Bas; Kompanje, Erwin J. O.; Moeliker, Cornelis W.
Abstract: Inspired by Jackass (a tv-show about self-injuring stunts), some friends topped off a drinking party with live fishes from their aquarium. After the goldfishes had gone down smoothly, a bronze catfish was ingested. Unaware of the morphology and anti-predator behaviour of this species, a healthy but intoxicated 28-year-old man got a surprise. The catfish erected and locked the spines of its pectoral fins and got lodged in the hypopharynx. After several hours, he presented himself at the emergency department with dysphonia and dysphagia. The fish had to be removed endoscopically. Intubation and admittance to the intensive care unit was necessary due to laryngeal oedema. Two weeks postoperatively, the patient made a full recovery and donated the fish to the Natural History Museum Rotterdam. The publicity generated by public exhibition of the 'do-not-swallow-fish' emphasised the official Jackass warning: '.. do not attempt any of the stunts you're about to see'.